Chemical characterization and evaluation of the antioxidant potential of gabiroba jam (Campomanesia xanthocarpa Berg) - doi: 10.4025/actasciagron.v35i1.14389 - Santos, Marli da Silva; Lima, Jair José de; Petkowicz, Carmen Lúcia de Oliveira; Cândido, Lys Mary Bileski (Acta Scientiarum. Agronomy, 2012)
Four formulations of gabiroba jam were processed, and their physicochemical and functional characteristics, rheological profile and jam acceptance were assessed. The physicochemical and chemical characteristics evaluated were water activity, titratable acidity, pH, reducing and non-reducing sugars, proteins, ashes, dietary fibers, color, and firmness. For functional analyses of the formulations, vitamin C, phenolic compounds and carotenoid contents were determined. The ABTS+ and DPPH· methods were employed to evaluate the antioxidant potential. Rheological analysis was performed in a HAAKE RS 75 Rheoestress rheometer with a plate/plate sensor. The flow curve behavior was adjusted using the Power Law and Herschel-Bulkley models. Sensory analyses were performed by 52 untrained testers using a 9-point structured hedonic scale. The content of total phenolic compounds in the jam was between 322.09 and 728.48 mg 100 g-1. The variation of vitamin C content was 97.39 to 123.39 mg 100 g-1. The samples also showed good retention of beta carotene. All samples showed a higher storage modulus (G’) than loss (G”) Thsensory evaluation revealed a satisfactory acceptance of the gabiroba jam formulations.